Cancer mortality in former East and West Germany: a story of unification?. Issue 1 (December 2017) - Medenwald, Daniel; Vordermark, Dirk; Dietzel, Christian
Abstract Background Health and social conditions vary between West and East Germany. Methods We analyzed annual mortality data of all recorded deaths caused by lung, colorectal, breast and prostate cancer in Germany as they are published by the Federal Bureau of Statistics (FBS) encompassing the period 1980–2014 for former West Germany (WG) and 1990–2014 for former East Germany (EG). To compare East and West Germany we computed the ratio of the mortality rates in both parts (mortality rate ratio, MRR, <1 indicates a lower mortality in EG). Forecasting methods of time series analyses were applied (model selection based on the Box/Jenkins approach) to predict 5-year trends until 2019. Results Lung cancer: In women mortality rose in both regions (WG: +2.8%, 1991–2014, EG: +2.2%, 1990–2014). In men mortality in WG declined between −2.1% and −1.2%, and by −2.7% (1993–2009) in EG which was followed by a plateau. Colorectal cancer: A decline was found in both WG (−3.1%, 1993–2014) and EG women (−3.8%, 1993–2008 and −2.0%, 2008–2014). A decline in EG men since 1992 (−0.9%, 1992–1997 and −2.3%, 1997–2014) mirrors the development in WG (−2.6%, 1995–2014). Breast cancer: Constant mortality decline in WG after 1996. In EG a decline (−2.4%, 1992–2007) was followed by a plateau with an MRR <1 (1990–2014). Prostate cancer: In WG a decline (−3.4%) came to a hold after 2007, while there was a constant decline of 1.5% in EG. The forecast indicated that mortality of colorectal/lung cancer in men and breast cancer reaches a plateau in future years. Conclusion Courses of mortality were similar between East and West, while existing differences are likely to remain in the near future.